Diagnostic and Epidemiologic Features of Visceral Leishmaniasis Transmission by The Phlebotomus Fly in Children Admitted to The Children’s Hospital in Benghazi - Garboui, Samira S. (Scientific Journal of University of Benghazi, 2021)
The Leishmania species are the causative agents of leishmaniasis, which is typically transmitted between vertebrate hosts through the bite of blood-sucking female phlebotomine sand flies. This study was conducted due to the paucity of information in the literature relevant to visceral leishmaniasis (VL) in Libyan children. The emergence of visceral leishmaniasis is of concern in Libya and is endemic in certain regions. Diagnosis of visceral leishmaniasis was based on patient history, physical results, and then confirmed by laboratory bone marrow examination. A cross-sectional, hospital-based study was conducted from the 1st of January 2013 to the 31st of December 2019 to investigate the epidemiological factors of VL in children admitted to the Children Hospital in Benghazi, Libya. The results indicated that during the study period there were 51 children diagnosed with VL among 99 suspected cases. The most common clinical symptoms were myelopoiesis (90.9%), aspiration (90.9%), cellularity (89.9%), erythropoiesis (88.9%), megakaryopoiesis (88.9%), hepatosplenomegaly (58.6%) and prolonged fever (48.5%). Children in the age group ≥3 years were most affected, and the male-female ratio was 2: 1. The highest number of cases of children were from the rural city of Murzuq at 45.5%. The study concluded that VL is an endemic health threat affecting children and adults in Libya. Considering that a portion of locally identified Leishmania donovani strains possess the ability to vascularize, it will be important to carefully understand the characteristics of transmission, increase professional and community awareness as well as improving prognosis and the availability of appropriate methods of treatment.